2019
DOI: 10.1177/0031512519892390
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Effects of Enhanced Expectancies for Motor Learning in Individuals With High and Low Self-Efficacy

Abstract: Previous research has shown that enhanced expectancies can foster a person’s motivational state and facilitate motor learning. However, the effects of enhanced expectancies on motivational state and subsequent motor learning in individuals with varied motivational states (e.g., self-efficacy; SE) are not well understood. This study examined the effects of enhanced expectancies on motivational state and motor learning in individuals with high and low SE by manipulating the type of knowledge of results (KR). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Based on the OPTIMAL theory, practice conditions that facilitate motor performance and learning are (a) enhanced expectancies, (b) autonomy support and (c) external focus of attention. In this theory, enhanced expectancies and autonomy support are con sidered as motivational factors and have been well investigated by previous research [7,9,13,14]. In addition, external focus of attention is consid ered as an attentional factor, which optimizes performance and learning a new motor skill [24].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the OPTIMAL theory, practice conditions that facilitate motor performance and learning are (a) enhanced expectancies, (b) autonomy support and (c) external focus of attention. In this theory, enhanced expectancies and autonomy support are con sidered as motivational factors and have been well investigated by previous research [7,9,13,14]. In addition, external focus of attention is consid ered as an attentional factor, which optimizes performance and learning a new motor skill [24].…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy is, for the most part characterized as the conviction in one's capacity to succeed in particular circumstances or to perform a skill (2). Several studies have tested the effects of the instructions based on the motivational and attentional factors in the OPTIMAL theory (i.e., enhanced expectancies, AU, and external focus of attention) and found that these factors positively affect performance and self-efficacy in a variety of motor tasks and across a range of age groups (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%